STUDI TENTANG FAKTOR â FAKTOR YANG MEMPENGARUHI PERTUMBUHAN DAN PERKEMBANGAN PADA BALITA DI DESA PENGALANGAN RW 03 MENGANTI GRESIK - ., Dianita Primihastuti, (D3 Kebidanan, 2013)
Growth and development is the main thing, it is essential and distinctive in children that are different but inter-related and difficult to separate. Several factors influence the process of growth and developments; internal factors and external factors that include nurturing environmental factors, stimulating factors and nutritional factors. Among these various factors, one more factor affecting the growth and development process is nurturing environment factors. If the parenting environment is better than the growth and development of infants would be better, whereas, if the parenting environment is not good, then the toddlers growth and development would become less good. Based on the results of observations made by the author in Pengalangan village, RW 03 Menganti Gresik, It was found that many toddlers who werelate in growth and development. The research design of this study was